Prevalência de sintomas de ansiedade e depressão em pacientes com diabetes tipo 2 com e sem dependência nicotínica e em tabagistas não diabéticos - Osme, Simone Franco (2012)
Introduction: Diabetic individuals who are smokers have higher risks of cardiovascular disease, premature death, and microvascular complications. The present study aims to evaluate the degree of nicotine dependence and the prevalence of symptoms of anxiety and depression in smokers with type 2 diabetes mellitus (T2D). Methods: Each of the T2D smoking patients treated at the Endocrinology Clinic of the Hospital de Clinicas, Federal University of Uberlândia, was matched with two controls. Thus, three study groups were formed: 46 T2D smokers (DS), 46 T2D non-smokers (D), and 46 smokers without diabetes (S), totaling 138 participants. The presence of symptoms of anxiety and depression was determined based on the Hospital Anxiety and Depression (HAD) scale, and the Fagerström Test for Nicotine Dependence was used to evaluate the degree of nicotine dependence. Results: The prevalence of high nicotine dependence among smokers with and without T2D was 39.1% and 37.1%, respectively (p = 0.999). There was no significant difference in the proportion of individuals with symptoms of anxiety in the DS group (50%) compared to group D (39.1%) or S (63%) (p = 0.072). The same was observed for symptoms of depression in groups DS, D, and S (30.4%, 39.1%, and 32.6%, respectively, p = 0.657). The consumption of anxiolytics in the DS group (19.6%) was higher than in group D (2.2%) (p = 0.028). Among male patients, the diabetic smokers had a higher prevalence of anxiety symptoms (19.6%) than non-smokers (2.9%) (p = 0.003). The prevalence of symptoms of anxiety and depression among nicotine addicts (54.6% and 37.1%, respectively) and non-addicts (57.7% and 28.1%, respectively) was similar. Conclusions: The prevalence of depression and anxiety among diabetic and non-diabetic smokers and diabetic non-smokers is similar, although the consumption of anxiolytics among diabetic smokers is significantly higher than diabetic nonsmokers. Diabetic male smokers have more symptoms of anxiety than non-smokers with diabetes. There is no difference in the prevalence of nicotine dependence among diabetics and non-diabetics. The presence of anxiety or depression symptoms is similar between individuals who are dependent and not dependent on nicotine.